Acute resuscitation with polyethylene glycol-20k: A thromboelastographic analysis. Issue 2 (August 2019) - Wickramaratne, Niluka; Kenning, Kristine; Reichstetter, Heather; Blocher, Charles; Li, Ru; Aboutanos, Michel; Mangino, Martin J.
Abstract : BACKGROUND: Previous ex vivo studies have shown that polyethylene glycol-20, 000 Da (PEG-20k), a novel synthetic polymer that is highly effective for resuscitation, has a hypocoagulable effect on human blood. This study's objective was to determine the in vivo effects of PEG-20k-based resuscitation solutions on coagulation and platelet function in a porcine model of hemorrhagic shock. METHODS: Anesthetized pigs underwent controlled hemorrhage until the lactate reached 7 mmol/L or 50% to 55% of their estimated blood volume was removed. A laparotomy was performed to simulate tissue injury. Low volume resuscitation (LVR) was given with fluorescein isothiocyanate-labeled 10% PEG-20k solution (100 mg/mL) or Lactated Ringers, both delivered at volumes equal to 10% of the estimated blood volume (n = 5). Thromboelastography was performed after surgery (baseline), after hemorrhage, and 15 minutes, 120 minutes, and 240 minutes postresuscitation. Hemoglobin was measured to determine changes in plasma volume. Plasma PEG-20k concentration was measured by indicator dilution. RESULTS: Pigs given PEG-20k survived 2.6-fold longer than controls ( p < 0.001) and had a significant increase in plasma volume demonstrated by the sustained drop in hemoglobin, relative to controls. Pigs resuscitated with LR died from hypotension an average of 90 minutes after resuscitation compared to the PEG-20k pigs, which all survived 240 minutes and were then euthanized with normal blood pressure and lactate. Administration of PEG-20k primarily decreased the thromboelastograph maximum amplitude, however this began to return toward baseline by 240 minutes. Peak plasma concentration of PEG-20k after LVR were 40% lower than predicted, based on simple dilution (5.7 mg/mL vs. 10 mg/mL) and the half-life was 59.6 minutes. CONCLUSION: These data demonstrate that acute resuscitation with PEG-20k significantly improves tolerance to hypovolemia but also decreases platelet function in the coagulation cascade, which was due, in part, to its volume expanding effects.